Effect of a Simulation-Based Educational Video on Menarche Readiness Among Fourth-Grade Girls in Yogyakarta - Wahyuni Idvia Nova; Andari Wuri Astuti; Djauhar Ismail (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2026)
Introduction: Menarche is a key biopsychosocial milestone in early adolescence, yet many young girls experience it with limited knowledge and emotional readiness due to inadequate, age-appropriate reproductive health education. This lack of readiness stems from insufficient understanding, limited information provided by parents and teachers, and suboptimal reproductive health education in schools. Providing education that is both comprehensive and age-appropriate about the physical and emotional changes of puberty is essential to help reduce fear, correct misconceptions, and lessen the stigma associated with menstruation. Methods: The study aimed to analyze the effect of simulation-based video media on adolescent readiness to face menarche. This study employed a pre-experimental design with a one-group pretest-posttest approach. The sample comprised 54 fourth-grade female students within elementary school, selected via total sampling. The research instrument was a questionnaire assessing readiness to face menarche. The intervention video presented realistic scenarios depicting the physical and emotional experiences associated with menarche, including hygiene management and coping strategies for discomfort, to support both cognitive and affective learning. Results: The analysis revealed an increase in readiness scores following the intervention, with a pretest mean of 15.44 and a posttest mean of 18.40. The Wilcoxon Signed Rank Test yielded a p-value of 0.000 (p < 0.05), indicating a significant effect of simulation-based video media on adolescent readiness to face menarche. Simulation-based video media effectively enhances adolescent readiness to face menarche and serves as a viable alternative for reproductive health education in elementary schools. Conclusion: This media can be implemented as an effective and practical method for delivering reproductive health education in primary school settings. It also serves as a feasible tool to support adolescents’ preparation for menarche by improving their readiness and understanding of this developmental milestone.